REINFORCEMENT THE ROLE OF INTELLIGENCE THROUGH SURVEILLANCE POSTS IN EACH WORK AREA OF THE IMMIGRATION OFFICE - Achmad Setiawan S (Journal of Law and Border Protection, 2019)
Indonesia is the largest island nation in the world consisting of 17,508 islands spread from sabang to merauke. This area of course in addition to having a positive impact in the maritime sector can also be a threat to the sovereignty of the country. With the continued increasing flow of international migration comparable to the level of immigration violations that occur. Therefore, this article will discuss the effectiveness of the implementation of immigration intelligence tasks and functions in Indonesia. The research uses qualitative approach by using secondary data that includes books, laws and regulations, and scientific journals as well as various other literature. The results showed that immigration intelligence carries out the duties and functions of intelligence investigation and security. The implementation of intelligence tasks and functions carried out by the Directorate General of Immigration and the Immigration Office upt in general is quite good, but sometimes there are still some violations that escape surveillance. Therefore, in an effort to optimize the role of immigration intelligence, it is considered necessary to establish intelligence posts in each area of work of the immigration office for the effectiveness of the implementation of intelligence officers in the field.